2014
DOI: 10.1039/c4ob00233d
|View full text |Cite
|
Sign up to set email alerts
|

Lewis acid-promoted cyclization/halogenation of allenyl ethenetricarboxylates and the corresponding amides: stereoselective synthesis of haloalkenyl five-membered heterocycles

Abstract: Lewis acid-promoted intramolecular reactions of allenyl ethenetricarboxylates and the corresponding amides have been examined. Reactions of allenyl ethenetricarboxylates and the amides with Lewis acids such as AlCl3, AlBr3 and ZnX2 (X = Cl, Br, I) gave 3,4-trans haloalkenyl five-membered heterocycles stereoselectively. The stereochemistry was determined by NOE experiments and reduction of the cyclized products. Various transformations of the haloalkenyl functionalized cyclic compounds have also been performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…[1][2][3][4][5][6] The requisites of this type of cyclization are an electrophilic alkene (such as diethyl 2-arylidene malonate) bearing coordination site for metal halides and an alkyne which acts as the nucleophile. While the analogous ene-ene cyclization [7][8][9][10][11][12][13][14][15][16] is facile, enyne cyclization is less facile due to low nucleophilicity of alkyne and thus often requires highly electrophilic olefin containing three electron-withdrawing groups. Snider et al showed that in the presence of stoichiometric amount metal halide containing nucleophilic ligand such as FeCl 3 , enyne triester of type 1 undergoes intramolecular cyclization to compound 2 (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] The requisites of this type of cyclization are an electrophilic alkene (such as diethyl 2-arylidene malonate) bearing coordination site for metal halides and an alkyne which acts as the nucleophile. While the analogous ene-ene cyclization [7][8][9][10][11][12][13][14][15][16] is facile, enyne cyclization is less facile due to low nucleophilicity of alkyne and thus often requires highly electrophilic olefin containing three electron-withdrawing groups. Snider et al showed that in the presence of stoichiometric amount metal halide containing nucleophilic ligand such as FeCl 3 , enyne triester of type 1 undergoes intramolecular cyclization to compound 2 (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…The requisites of this type of cyclization are an electrophilic alkene (such as diethyl 2‐arylidene malonate) bearing coordination site for metal halides and an alkyne which acts as the nucleophile. While the analogous ene‐ene cyclization [7–16] is facile, enyne cyclization is less facile due to low nucleophilicity of alkyne and thus often requires highly electrophilic olefin containing three electron‐withdrawing groups. Snider et al.…”
Section: Introductionmentioning
confidence: 99%